Identification and Mitigation of Stuck Pipe Problem During Cement Drill-Out Cement in XSF Well - Suranta, Bambang Yudho; Sofyan, Akhmad; Siahan, Paradongan; Sidiq, Asep (Scientific Contributions Oil and Gas, 2026)
This study aimed to develop an integrated diagnostic framework to identify pack-off–type stuck pipe during cement drill-out operations and strengthen quantitative risk assessment for workover interventions. A stuck pipe event in the XSF well (9-5/8-in. section) at 724.42 m was investigated using drilling data, drill-string mechanics, drilling fluid evaluation, and hydraulic/cutting-transport analysis. The results of the mechanical assessment showed that excessive loading and overpull were unlikely primary causes of stuck pipe problem. However, the hydraulic and transport evaluation showed inadequate cutting removal, consistent with particle settling and progressive pack-off formation. To evaluate this event, a diagnostic classification matrix combining four operational indicators was applied, showing complete agreement with an established pack-off classification method. The pipe was ultimately freed after 99 hours using controlled tension-cycling with spotting-fluid support. Based on the transport analysis, this study recommended operational controls, which included maintaining a minimum circulation rate of 340 GPM and the use of shale shakers during cement removal to reduce pack-off risk. Furthermore, the prolonged liberation time showed the substantial cost impact of stuck pipe problem, supporting the economic case for preventive implementation.